1997
DOI: 10.1136/bmj.315.7106.449
|View full text |Cite
|
Sign up to set email alerts
|

Size at birth, maternal nutritional status in pregnancy, and blood pressure at age 17: population based analysis

Abstract: Objective: To assess the effect of size at birth, maternal nutrition, and body mass index on blood pressure in late adolescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
66
3
3

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(75 citation statements)
references
References 23 publications
3
66
3
3
Order By: Relevance
“…The registry's design and methods have been described in detail elsewhere and it has been used for clinical and epidemiologic research in schizophrenia (Harlap et al, 1977;Lichtenberg et al, 1999). In the past decade, studies using the Jerusalem Perinatal Study, linked to other databases in Israel, showed that the offspring' identification numbers, sex, birth dates, and basic demographic information, including parental ages, were more than 99.9% accurate (Lichtenberg et al, 1999;Laor et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…The registry's design and methods have been described in detail elsewhere and it has been used for clinical and epidemiologic research in schizophrenia (Harlap et al, 1977;Lichtenberg et al, 1999). In the past decade, studies using the Jerusalem Perinatal Study, linked to other databases in Israel, showed that the offspring' identification numbers, sex, birth dates, and basic demographic information, including parental ages, were more than 99.9% accurate (Lichtenberg et al, 1999;Laor et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…6 -8 In children, some investigators have detected a decrease in systolic BP (SBP) from -1.48 6 to -2.80 mm Hg 7 for each 1-kg increase in birth weight. Alternatively, others have found a weak 9 or no 10,11 relationship of birth weight with BP during adolescence or in adults. Overall, there is, as yet, limited evidence in humans demonstrated by prospective data that birth weight as an indicator of the fetal environment contributes significantly to BP level in later life.…”
mentioning
confidence: 99%
“…Several human studies have described a positive correlation between maternal weight and/or adiposity and blood pressure of teenage children (Lawlor et al, 2004;Cho et al, 2000;Laor et al, 1997), leading Boney et al to conclude from their examination of large for gestational age babies and the incidence of childhood metabolic syndrome, that "given the increased obesity prevalence in children exposed to either maternal diabetes or maternal obesity, there are implications for perpetuating the cycle of obesity, insulin resistance, and their consequences in subsequent generations." Few, if any, of the studies in humans include offspring sex as a co-variable (Boney et al, 2005).…”
Section: Maternal Obesitymentioning
confidence: 99%